Plasma vitellogenin detection in males of the African sharptooth catfish, Clarias gariepinus, from Ikpoba and Osse Rivers, Southern Nigeria: a brief research report - Maurice E. Imiuwa; Lauretta Oghenevurie; Eneyeme J. Olowojoba; Duncan O. Onojeharo; Nora Adibor; Ese J. Emmanuel; Nancy E. Ugorji; Sydney E. Osifo (Frontiers in Environmental Science)
The impact of endocrine disrupting chemicals (EDCs) on humans and wildlife ranks amongst the most insidious of environmental health concerns. Sadly, the paucity of scientific data on environmental presence of EDCs in developing countries, especially those of Africa, has recently been described as a major setback to understanding their region-specific impact and management focus. Induction of plasma vitellogenin (Vtg) in male oviparous fish has been employed across the globe as a biomarker of exposure to estrogenic EDCs. However, despite initial laboratory validation of the suitability of males of Clarias gariepinus (which has almost a Pan-African distribution) for understanding exposure to EDCs using plasma Vtg induction, plasma Vtg has not been detected in wild male C. gariepinus inhabiting EDC-polluted environment, even with a species-specific enzyme-linked immunosorbent assay (ELISA), and its suitability for biomonitoring EDCs in African freshwater environments remains to be demonstrated. In the present study, adult male C. gariepinus samples were collected from two major urban catchment-impacted rivers, and analysed for endocrine-related gonadal histopathology and plasma Vtg (using a sensitive commercially available non-species-specific fish Vtg ELISA). Plasma Vtg was detected in male C. gariepinus from all sampling sites, while the gonads had normal (histo)morphology. The findings, contrasting previous reports, strongly suggest that wild males of this species are suitable for biomonitoring EDCs in African freshwater environments. Furthermore, the development of a commercially available Vtg ELISA, specifically for this species (with detection limit and sensitivity comparable to the one used in the present study), might be worth considering.